The Favorable Allele of CAPN1-316 Genetic Marker is Absent in Bali and Sumbawa Cattle - Shidiq, Fajrin; Anwar, Saiful; Lestari, Novi Cahya; Kusdianawati, Kusdianawati (Faculty of Animal Science, Universitas Brawijaya, 2023)
The micromolar calcium-activated neutral protease 1 (CAPN1) gene encodes the u-calpain enzyme, which plays a crucial role in meat tenderisation. Genetic diversity within the CAPN1 gene, specifically a nucleotide substitution from G to C in exon nine resulting in a change from glycine to alanine at position 316 (CAPN1-316 marker), is known to significantly affect meat tenderness. This study aimed to assess the polymorphism of the CAPN1-316 locus in Bali and Sumbawa cattle. A total of 293 blood samples, 193 from Bali cattle and 100 from Sumbawa cattle were extracted and genotyped using PCR-RFLP with BtgI restriction enzyme (recognition sequence: 5'-C*CRYGG-3') applied to 706 bp PCR products. The results showed the presence of only one genotype (GG genotype) and one allele (G allele) in all DNA samples obtained from the Bali and Sumbawa cattle populations studied. In conclusion, the CAPN1-316 genetic marker showed a lack of diversity or monomorphism in Bali and Sumbawa cattle, making it unsuitable for further association studies in these breeds. Consequently, the CG/AG haplotype identified in Sumbawa cattle warrants further investigation and could serve as an alternative genetic marker, especially due to its monomorphism at the CAPN1-316 locus.